Global Research Trend of Islamic Banking Window: A Bibliometric Analysis - Shofina Firdausi; Muhamad Subhi Apriantoro (Universitas Muhammadiyah Surakarta, 2025)
Purpose: To examine the development, contribution, and intellectual structure of research on Islamic banking windows through a comprehensive bibliometric analysis of publications indexed in Scopus. Methodology: This study employs a bibliometric approach using Scopus-indexed publications related to Islamic banking windows. The analysis covers publication trends over time, leading countries, prolific authors, and affiliated institutions to map the research landscape and intellectual structure of the field. Results: The findings reveal a growing trend in publications on Islamic banking windows, with contributions concentrated in specific countries, authors, and institutions. The bibliometric mapping highlights key research themes and demonstrates the increasing role of Islamic banking windows in the global banking literature. Applications/Originality/Value: This study provides a systematic and comprehensive overview of Islamic banking windows research, offering valuable insights for academics, practitioners, and policymakers. It contributes original value by mapping the intellectual structure of the field and identifying research gaps that can inform future studies and strategic development in Islamic banking.